Factors associated with adolescent birth in Indonesia: a national survey - Yuli Devi; Mario Ekoriano; Diah Sari; Muthmainnah Muthmainnah (James Cook University, 2022)
Introduction: Adolescent birth has many negative impacts on the development of a country. Preparing for pregnancy needs to be done from adolescence so that adolescents and women are healthy during pregnancy and give birth to healthy babies. In Indonesia, the adolescent birth rate is still high. This study aimed to identify the determinants of adolescent birth (birth at ages 15-19 years) in Indonesia. Methods: This study was a quantitative study using secondary data from the 2019 Government Performance and Accountability Survey, the result of a collaboration between the National Population and Family Planning Board and Central Bureau of Statistics, with representative sample coverage at province and national levels (n=7786). Simple and multiple logistic regression tests were used to analyze data in this study. Results: Total responses in this study were 7786, of whom 373 had had an adolescent birth (4.8%). Significant factors for adolescent birth were working, coming from a rural area, having a low level of welfare and first having sexual intercourse at ages 15-19 years. Level of education, having information on family planning, having access to print or electronic media, and age at first marriage had no significant effect on adolescent birth. Conclusion: This study concludes that the most influential factor for adolescent birth is the age of first having sexual intercourse. The authors suggest designing media more suitable to the needs of adolescents to prevent early sexual intercourse and reduce the high adolescent birth rate in Indonesia.